Disease Threat and the Functional Flexibility of Ingroup Derogation - Wu, Qi; Yang, Shuang; Zhou, Ping (Frontiers in Psychology, 2019)
While the findings from previous studies directly relate the ingroup derogation phenomenon to the evolved response of the behavioral immune system, there are three major limitations in the previous studies on the functional flexibility of ingroup derogation. The present study further investigated the functional flexibility of ingroup derogation by conducting three behavioral experiments on Chinese participants. In Experiment 1, we tested whether exposing to situational disease primes leads to an exaggerated ingroup derogation attitude by adopting a more rigorous control. In Experiment 2, we manipulated the source of disease threats to test whether the ingroup derogation mechanism adjusts its response according to the specific perceived vulnerabilities to the disease threats posed by ingroup and outgroup members. In Experiment 3, we tested whether recent illness promotes the expression of ingroup derogation attitudes. Results of the three experiments consistently showed that, the Chinese participants adjusted their ingroup derogation attitudes according to the external environmental disease cues (Experiment 1 & 2) and the internal physiological disease cues (Experiment 3). The results also showed that the ingroup derogation mechanism was sensitive to the specific perceived vulnerabilities to the ingroup disease threat and the outgroup disease threat (Experiment 2). Taken together, these results support the evolutionary hypothesis of ingroup derogation and suggest that the ingroup derogation found in East Asian cultures could be accounted by a functionally flexible disease-avoidance mechanism.